An Akkadian Text about Metrics and Sizes - عمران د. نشاة علي (مجلة دراسات في التاريخ والآثار, 2020)
Among the many confiscated cuneiform tablets in the Iraqi Museum from unknown provenance, the tablet IM. 204709 has been selected for this study. The reason for selecting this tablet is its rare subject matter on providing numerical data for the digging of irrigation canals. The paleography and writing style suggests that this text, as well as the other texts in the collection, date to the Akkadian Dynasty (ca. 2371-2255 BCE), and derived from illegal excavations at the ancient city of Umma (modern Jokha) in southern Iraq (Foster 1982). The tablet is rectangular in shape and measures 6 x 4 cm, and it has five lines in the obverse (fig.1) and two lines in the reverse (fig.2); these two lines